PENGARUH KUALITAS KEHIDUPAN KERJA DAN DUKUNGAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (Students' Journal of Accounting and Banking, 2013)
The study ecxamines the impact between quality of work life and organizational support to organizational commitment with job satisfaction as a mediated to employees at Sekretariat Daerah Kabupaten Pati. The purpose of this study is to find empirical evidence about the presence / the absence of b). the positive effect of organizational support and job satisfaction, a). the positive effect of quality of work life and job satisfaction, d). the positive effect of organizational support and organizational commitment, c). the positive effect of quality of work life and organizational commitment, e). the positive effect of job satisfaction and organizational commitment, g). the effect of organizational support and organizational commitment with job satisfaction as a mediated and f). the effect of quality of work life and organizational commitment with job satisfaction as a mediated. The respondent of this study are the employees at Sekretariat Daerah Kabupaten Pati, which amount 227 employees and the research used purposive sampling technique method. To analyse the research instrument used validity test with factor analysis, and reliability test with alpha cronbach, and multiple linier regression, and t statistics to prove the research hypothesis and mediated effect to test job satisfaction as mediated variable. The result show that quality of work life and organizational support have positive and significance effect to job satisfaction, organizational support, quality of work life and job satisfaction have positive and significance effect to public civil servant performance that prove with significancy level.  and quality of work life and organizational support have indirect effect to organizational commitment with job satisfaction as a mediated variables Keywords : organizational support, quality of work life job satisfaction, and organizational commitment